2020
DOI: 10.3390/ijerph17155329
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Pb, Zn, Cd, and Mn Removal from Karst Water by Eichhornia crassipes

Abstract: This study experimentally investigated heavy metal removal and accumulation in the aquatic plant Eichhornia crassipes. Pb, Zn, Cd, and Mn concentrations, plant morphology, and plant functional groups were analyzed. Eichhornia crassipes achieved high removal efficiency of Pb and Mn from karst water (over 79.5%), with high proportion of Pb, Zn, and Cd absorption occurring in the first eight days. The highest removal efficiencies were obtained at initial Pb, Zn, Cd, and Mn concentrations of 1 mg/L, 2 mg/L, 0.02 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
(48 reference statements)
1
7
0
1
Order By: Relevance
“…The uptake and accumulation of Mn in water hyacinths in all experiments showed that the plants were able to uptake and store Mn in the submerged parts (roots) more than in the shoots (stems leaves). This is consistent with the findings of Zhou et al [ 38 ], who examined the removal and accumulation of heavy metals, such as Mn, Pb, Zn, and Cd, in water hyacinths in hard water and discovered that floating plants had the greatest Mn removal capacity, including plants that had accumulated Mn in their roots in higher quantities than in their stems. Therefore, in this study, pH 5-treatment with SP (SP:Cu1:3 M ratio) resulted in the maximum accumulation rate of Mn in the submerged parts (roots) of floating plants, which absorbed and accumulated Mn in high quantities after seven days, with a value of 9764.19 ± 357.36 mg/kg, as shown in Fig.…”
Section: Resultssupporting
confidence: 91%
“…The uptake and accumulation of Mn in water hyacinths in all experiments showed that the plants were able to uptake and store Mn in the submerged parts (roots) more than in the shoots (stems leaves). This is consistent with the findings of Zhou et al [ 38 ], who examined the removal and accumulation of heavy metals, such as Mn, Pb, Zn, and Cd, in water hyacinths in hard water and discovered that floating plants had the greatest Mn removal capacity, including plants that had accumulated Mn in their roots in higher quantities than in their stems. Therefore, in this study, pH 5-treatment with SP (SP:Cu1:3 M ratio) resulted in the maximum accumulation rate of Mn in the submerged parts (roots) of floating plants, which absorbed and accumulated Mn in high quantities after seven days, with a value of 9764.19 ± 357.36 mg/kg, as shown in Fig.…”
Section: Resultssupporting
confidence: 91%
“…The results obtained do not show a higher concentration of heavy metals and heteroatoms such as nitrogen, phosphorus, and sulfur, coinciding with previous results [59], in contrast to the high content of heavy metals found on non-lignocellulosic biomass. Therefore, they do not show toxic metals, as found in some cases in non-lignocellulosic biomass, which can dissolve in water and lead to contamination and accumulation in food chains [60].…”
Section: Principal Major and Minor Elements Of Compositionmentioning
confidence: 99%
“…The spectral peaks at 3437 cm − 1 , 2923 cm − 1 , and 1635 cm − 1 represented O-H, C-H, and C = O stretching vibration, respectively. However, the organic group C = O is present in proteins, amino acids, peptides, carbohydrates, and lipids [39] . For the prepared composite material (WHLPC/GO/CS/PVA), peaks were obtained at 3450 cm − 1 , 2923 cm − 1, and 1641 cm − 1 showing that O-H, C-H, and C = O functional groups were introduced to the new prepared composite.…”
Section: Xrd and Ftir Characterization Of Whlpc/go/cs/pvamentioning
confidence: 99%